2007
DOI: 10.1007/s10669-007-9055-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune stimulation in fish and chicken through weak low frequency electromagnetic fields

Abstract: A hypothesis is proposed how Low Frequency Electromagnetic Field (LF EMF) exposure can stimulate an immune response, based on recent insights in immunology. We hypothesize that the Immunent EMF treatment induces mild stress to cells, which then produce cytokines that function as alarms or so called danger signals for the immune system. In this way EMF treatment takes the place of multiplying pathogens, and the damage these cause, in the triggering of an immune response. In a first series of experiments in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…showed less DNA damage) compared to cells exposed to the mutagen only [14] . Other similar examples have been reported in the literature [2 , 24] , and therefore, this phenomenon requires further investigation.…”
Section: Introductionsupporting
confidence: 71%
“…showed less DNA damage) compared to cells exposed to the mutagen only [14] . Other similar examples have been reported in the literature [2 , 24] , and therefore, this phenomenon requires further investigation.…”
Section: Introductionsupporting
confidence: 71%
“…Dose-dependency of PEMF effects is generally very steep and has been described for different systems to occur below 1 mT [10], below 500 nT [29] and even below 50 nT [30]. It appears that the two field strengths used in our study (0.4 and 1.1 mT) both induced the maximum effect.…”
Section: Discussionsupporting
confidence: 53%
“…Thresholds for PEMF effects on living systems have been estimated at 500 nT [29] and even 50 nT [30]. Flux density was measured in our study at five distances from the coils with flux density values between 1 mT and 0.1 mT.…”
Section: Discussionmentioning
confidence: 95%
“…Single publications from laboratory studies have identified detectable effects of ELF on bacteria (50 Hz, 0.1 -1.0mT: Cellini et al 2008), Daphnia (50Hz and above: Krylov 2008), and in vitro preparations from fish and chickens (200 Hz and above, [1.5-5mT]: Cuppen et al 2007).…”
Section: Elf Fieldsmentioning
confidence: 99%